Evaluation of Colour Versions of Wild Sage (Salvia nemorosa L.) - Kaprinyák, T.; Koronkai, J.; Zsiláné, A. A.; Szakadát, Gy.; Lévai, P.; Kováts, Z.; Fári, M. (International Journal of Horticultural Science, 2013)
In the continental weather zone, more and more frequently occurring extreme conditions require continuous renewal of the market which generates constant challenge for the ornamental plant breeders. Most of the traditionally used decorative ornamental plants are sensitive to these extreme conditions. In 2001, Department of Plant Biotechnology, Debrecen University initiated an interdisciplinary breeding program in collaborations with Zoltan Kovats (he dealt with hungarian drought-tolerant plant species) to produce new or reintroduce forgotten drought-tolerant ornamental species into public parks and roadsides. From ~900 species of Salvia genus, Salvia nemorosa L. has been known as a medical plant, however, because of its high adaptation ability and decorative nature it is a highly recommended ornamental plant as well. Salvia nemorosa L. has a low maintenance, extremely droughttolerant, fast growing plant, generates proper cover, and highly competing weeds on roadsides. Nowadays, 50-60 varieties are available; however this number could be increased by new hybrids. Great morphological and colour variation could be seen within the species, from different white to deep violet. The main goal of this research is the production of elite lines with wide colour and morphological variation in wild sage. We have already obtained 25 different clones for further investigation without eliminating the original plants generating an in vitro gene bank as it has been done by Italian breeders.